Benefits of Condensed Tannins in Forage Legumes Fed to Ruminants: Importance of Structure, Concentration, and Diet Composition. Issue 3 (1st May 2019) - Mueller-Harvey, Irene; Bee, Giuseppe; Dohme-Meier, Frigga; Hoste, Hervé; Karonen, Maarit; Kölliker, Roland; Lüscher, Andreas; Niderkorn, Vincent; Pellikaan, Wilbert F.; Salminen, Juha-Pekka; Skøt, Leif; Smith, Lydia M.J.; et al.
Abstract : Condensed tannins (CTs) account for up to 20% of the dry matter in forage legumes used as ruminant feeds. Beneficial animal responses to CTs have included improved growth, milk and wool production, fertility, and reduced methane emissions and ammonia volatilization from dung or urine. Most important is the ability of such forages to combat the effects of gastrointestinal parasitic nematodes. Inconsistent animal responses to CTs were initially attributed to concentration in the diet, but recent research has highlighted the importance of their molecular structures, as well as concentration, and also the composition of the diet containing the CTs. The importance of CT structural traits cannot be underestimated. Interdisciplinary research is the key to unraveling the relationships between CT traits and bioactivities and will enable future on‐farm exploitation of these natural plant compounds. Research is also needed to provide plant breeders with guidelines and screening tools to optimize CT traits, in both the forage and the whole diet. In addition, improvements are needed in the competitiveness and agronomic traits of CT‐containing legumes and our understanding of options for their inclusion in ruminant diets. Farmers need varieties that are competitive in mixed swards and have predictable bioactivities. This review covers recent results from multidisciplinary research on sainfoin ( Onobrychis Mill. spp.) and provides an overview of current developments with several other tanniniferous forages. Tannin chemistry is now being linked with agronomy, plant breeding, animal nutrition, and parasitology. The past decade has yielded considerable progress but also generated more questions—an enviable consequence of new knowledge!